A Meta-Synthesis Study on Students’ Motivation and their English Achievement - Haryanti, Sri; Yuwono, Suhud Eko; Setyandari, Ana; Widayanti, Sukasih Ratna (International Journal of Active Learning, 2024)
This research aims to answer the problems: 1) Does students' learning motivation have a close relationship with their English achievement? and 2) How is the relationship between students' learning motivation and their English achievement? It is hoped that the results will be useful for English language observers who want to know more about English learning achievements which are influenced by learning motivation and for students as motivation for learning English. The population in this research is scientific publication articles in journals about students’ motivation and their English achievements in the last ten years 2013-2023. The sample in this research is a scientific publication article about achievement motivation in English learning. Research articles have the following categories: 1) Articles are created by public researchers and students; 2) Articles use qualitative, quantitative, qualitative and quantitative strategies; 3) Articles are about the possession of motivation to learn English in relation to student achievement; 4) Education levels are Junior High School, High School, College, and English course. In this study, researchers used the 'listening method' to collect data from works that discuss student motivation and their English language achievements in the last ten years. To test the validity of the data, researchers used source triangulation. This research is a meta-synthesis research with a qualitative approach carried out in three steps, namely preparation, action, and preparation of a research report. The research results show that students' learning motivation has a close relationship with their English language achievement, and 2) The relationship between students' learning motivation and English language achievement is interrelated. Motivation to learn English influences learning achievement. Learners who have high motivation in learning English achieve good results, while those who have low motivation to learn achieve less well.